Provider perspectives on the impact of COVID-19 on treatment of substance use and opioid use disorders among American Indian and Alaska Native adults - Meenakshi Richardson; Meenakshi Richardson; Meenakshi Richardson; Meenakshi Richardson; Katherine Hirchak; Katherine Hirchak; Katherine Hirchak; Kelsey Bajet; Kelsey Bajet; Kelsey Bajet; Mariah Brigman; Mariah Brigman; et al. (Frontiers Media S.A., 2024)
IntroductionAmerican Indian/Alaska Native (AI/AN) communities are more likely to suffer negative consequences related to substance misuse. The COVID-19 pandemic exacerbated the opioid poisoning crisis, in combination with ongoing treatment barriers resulting from settler-colonialism, systemic oppression and racial discrimination. AI/AN adults are at greatest risk of COVID-19 related serious illness and death. In collaboration with an Indigenous community advisory board and Tribal leadership, this study explored AI/AN treatment provider perceptions of client-relatives' (i.e., SUD treatment recipients) experiences during the pandemic from 2020 to 2022.MethodsProviders who underwent screening and were eligible to participate (N = 25) represented 6 programs and organizations serving rural and urban areas in Washington, Utah, and Minnesota. Participants engaged in audio-recorded 60-90 min semi-structured individual interviews conducted virtually via Zoom. The interview guide included 15 questions covering regulatory changes, guidance for telemedicine, policy and procedures, staff communication, and client-relatives' reactions to implemented changes, service utilization, changes in treatment modality, and perceptions of impact on their roles and practice. Interview recordings were transcribed and de-identified. Members of the research team independently reviewed transcripts before reaching consensus. Coding was completed in Dedoose, followed by analyses informed by a qualitative descriptive approach.ResultsFive main domains were identified related to client-relative experiences during the COVID-19 pandemic, as observed by providers: (1) accessibility, (2) co-occurring mental health, (3) social determinants of health, (4) substance use, coping, and harm reduction strategies, and (5) community strengths. Providers reported the distinctive experiences of AI/AN communities, highlighting the impact on client-relatives, who faced challenges such as reduced income, heightened grief and loss, and elevated rates of substance use and opioid-related poisonings. Community and culturally informed programming promoting resilience and healing are outlined.ConclusionFindings underscore the impact on SUD among AI/AN communities during the COVID-19 pandemic. Identifying treatment barriers and mental health impacts on client-relatives during a global pandemic can inform ongoing and future culturally responsive SUD prevention and treatment strategies. Elevating collective voice to strengthen Indigenous informed systems of care to address the gap in culturally-and community-based services, can bolster holistic approaches and long-term service needs to promote SUD prevention efforts beyond emergency response efforts.